FINANCIAL INCLUSION AND ITS DETERMINANTS: THE CASE STUDY OF KRISHNARAJANAGAR TALUK - Shashikala (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In this twenty first century, the society must take an active people centered and growth oriented poverty alleviation strategy- a strategy which seems to incorporate women’s aspirations, dynamism and involvement. It is envisaged that, the commercial Banks, RRBs and co-operative Banks have plays a vital role in such strategy. But there is a need for structural orientation of the groups of new business. Micro-credit movement has to be viewed from a long term perspective under SHG framework, which underlines the need for deliberate policy implications in favor of assurance in terms of technology back-up product market and human resource development. Hence, there is a need for the development of an innovative and diversified micro finance sector, which leads to a real contribution to financial inclusion of women and women empowerment. The present study makes an attempt to understand the role of SHGs in women empowerment in study area and how women are benefited through these SHGs. The study presents concepts of financial inclusion, SHGs and women empowerment.